Psychedelics as a treatment for disorders of consciousness. Issue 1 (21st April 2019) - Scott, Gregory; Carhart-Harris, Robin L
Abstract: Based on its ability to increase brain complexity, a seemingly reliable index of conscious level, we propose testing the capacity of the classic psychedelic, psilocybin, to increase conscious awareness in patients with disorders of consciousness. We also confront the considerable ethical and practical challenges this proposal must address, if this hypothesis is to be directly assessed.